2014
DOI: 10.3390/ijms15045199
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of Bone Morphogenetic Protein (BMP)-9 in Human Liver Diseases

Abstract: Bone morphogenetic proteins (BMP-2 to BMP-15) belong to the Transforming Growth Factor (TGF)-β superfamily and, besides their well-documented roles during embryogenesis and bone formation, some of them have recently been described to be involved in the pathogenesis of different organs, including the liver. The role of BMPs in liver damage responses including hepatocellular carcinoma (HCC) development has only begun to be addressed and strong evidence supports the concept of a pro-tumorigenic role of BMP signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 97 publications
(149 reference statements)
2
46
0
Order By: Relevance
“…Although BMP-9 is constitutively expressed in healthy liver,17 19 knowledge about its physiological functions is still very limited (for review, see45). Whereas inhibition of BMP-9/ALK1 signalling is already discussed as a potential anti-angiogenic strategy in cancer46 and clinical application of rhBMP-9 was recently presented as a potentially promising new approach to promote fracture healing,47 its possible roles during acute or chronic liver damage were only insufficiently investigated up to now.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMP-9 is constitutively expressed in healthy liver,17 19 knowledge about its physiological functions is still very limited (for review, see45). Whereas inhibition of BMP-9/ALK1 signalling is already discussed as a potential anti-angiogenic strategy in cancer46 and clinical application of rhBMP-9 was recently presented as a potentially promising new approach to promote fracture healing,47 its possible roles during acute or chronic liver damage were only insufficiently investigated up to now.…”
Section: Discussionmentioning
confidence: 99%
“…BMP9 was first identified in the developing mouse liver as playing an important role in regulating iron metabolism and the development of cholinergic neurons (39). BMP9 has been implied in tumourigenesis (7)(8)(9)(10)(11)(12)(13)16,(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the TGF-β superfamily of signaling ligands, which include BMPs, activins, and TGF-βs, bind to two types of transmembrane serine-threonine kinase receptors known as type I and type II receptors (62,63). BMPs comprise the largest group of ligands within the TGF-β family (64) and play an essential role in cellular processes including differentiation, proliferation, angiogenesis, apoptosis, and bone formation (65,66). In mammals, seven BMP type I receptors, (i.e., ALK 1–7), and three BMP type II receptors (i.e., BMPR-II, ActR-II and ActR-IIB) have been identified (62).…”
Section: Tgf-β Signaling and Regulation Of Oatp Transport Activitymentioning
confidence: 99%
“…Awell-characterized agonist for ALK1 is bone morphogenetic protein (BMP)-9, which plays a role in several cellular processes including differentiation, proliferation, angiogenesis, and bone formation (65,66,87). BMP-9 is primarily produced by the liver and is present in the systemic circulation at a concentration of 5 ng/mL, which is above its EC 50 (66) and has been shown to physiologically induce constitutive Smad1/5/8 phosphorylation in endothelial cells (88). In another study using human dermal microvascular endothelial cells, Smad1/5/8 activation was demonstrated in a dose-dependent manner with BMP-9.…”
Section: Tgf-β Signaling and Regulation Of Oatp Transport Activitymentioning
confidence: 99%